Carbon-nanotube-entangled Co, N-codoped carbon nanocomposite for oxygen reduction reaction. (23rd February 2021) - Liu, Haohui; Wang, Siyu; Long, Ling; Jia, Jianbo; Liu, Minchao
Abstract: The design of highly efficient and stable electrocatalysts for oxygen reduction reaction (ORR) is still a great challenge. Herein, we prepared Co, N-codoped carbon nanocomposites (Co@NC-ZM) with entangled carbon nanotubes. The large Brunauer–Emmett–Teller surface area (604.7 m 2 g −1 ), rich mesoporous feature, Co, N doping and synergetic effect between various species of Co@NC-ZM can expose more active sites and facilitate conductivity and mass transport. Benefiting from the above unique advantages, Co@NC-ZM exhibits excellent ORR performance with more positive onset potential (0.96 V) and half-wave potential (0.83 V) than those of commercial Pt/C (0.96 and 0.81 V, correspondingly). This work provides a new strategy for further exploring efficient non-precious-metal-based catalysts for ORR.